A framework for integrating syntax, semantics and pragmatics for computer-aided professional practice: with application of costing in construction industry - Xu, Shen; Liu, Kecheng; Tang, Llewellyn C.; Li, Weizi (Elsevier, 2016)
Producing a bill of quantity is a knowledge-based, dynamic and collaborative process, and evolves with variances and current evidence. However, within the context of information system practice in BIM, knowledge of cost estimation has not been represented, nor has it been integrated into the processes based on BIM.